Cadmium exposure triggers vimentin phosphorylation via SIRT6-regulated AKT/PI3K signaling pathway in COPD - Rajesh Sinha; Pooja Singh; Huaxiu Zeng; Abhishek Kumar; Veena B. Antony (European Journal of Cell Biology, 2025)
Chronic Obstructive pulmonary disease (COPD) is a global health concern affecting over 300 million individuals worldwide, with airway fibrosis and subsequent small airway narrowing identified as the primary mechanism driving disease progression. This pathological process is characterized by accelerating lung aging, manifesting as reduced cellular growth and increased expression of cyclin-dependent kinase inhibitors in fibroblasts, which we have demonstrated in our previous study utilizing a cadmium-induced COPD mouse model. Cadmium, a toxic heavy metal, penetrates deep into the lung airways inducing oxidative stress, promoting extracellular matrix deposition, and triggering inflammatory reactions. The present study elucidates that cadmium exposure results in the inhibition of sirtuin-6 (SIRT6) which promotes phosphorylation of the AKT/PI3K signaling pathway, which in turn leads to phosphorylation of vimentin, an intermediate filament protein. Cadmium increases extracellular vimentin which is phosphorylated through AKT/PI3K signaling due to SIRT6 inhibition. Vimentin inhibition using siRNA transfection study suggested no effect on SIRT6, phosphorylated AKT and PI3K expression. SIRT6 induction (UBCS039) in fibroblasts leads to a decrease in phosphorylated AKT/PI3K inhibiting extracellular vimentin levels (P = 0.0002) in cadmium-exposed cells. The present work proposes role of SIRT6 in regulation of vimentin, an important intermediate filament in pathogenesis of COPD.